A simplified analysis of rectangular floating plates subjected to moving loads. (15th March 2015) - Takabatake, Hideo
Abstract: A simplified analytical method for determining the preliminary design stage of rectangular very large floating plates, as for a floating international airport, is proposed in the closed form solution under the Kirchhoff-Love hypothesis and small deformation. The floating plates have both variable structural stiffness and variable spring stiffness. The variable structural stiffness is caused by local stiffness variations due to arbitrarily located voids, stiffened beams, and notches. These variations are expressed generally using the extended Dirac function proposed by Takabatake, H. (1991a, Int. J. Solids Struct. 28 (2), pp. 179–196.). On the other hand, the variable spring stiffness represents the variation in buoyancy forces produced by tidal changes in shallow coastal seas. The buoyancy forces are represented by the elastic foundation in the Winkler model. The interaction between the structure and the water is neglected by regarding the additional water action produced by the effect of the interaction as an additional external load previously given from another suitable method. The simplified closed-form solutions for the transverse vibration and forced vibration are presented using the Galerkin method. Also, the level of accuracy of the closed-form solutions proposed here is proven from numerical computations. Highlights: Present a simplified method to the mega floating plates subject to moving loads. Consider the variable structural stiffness and the variable spring stiffness. The floating force is modeled by the variable Winkler elastic model.